2015
DOI: 10.1186/s12967-015-0677-8
|View full text |Cite
|
Sign up to set email alerts
|

PEP-1-MsrA ameliorates inflammation and reduces atherosclerosis in apolipoprotein E deficient mice

Abstract: BackgroundMethionine sulfoxide reductase A (MsrA) is a potent intracellular oxidoreductase and serves as an essential factor that protects cells against oxidative damage. However, therapeutic use of exogenous MsrA in oxidative stress-induced diseases is limited, because it cannot enter the cells. The aim of this study is to investigate whether MsrA with PEP-1, a cell penetrating peptide, fused to its N-terminus can protect against oxidative stress in macrophages and can attenuate atherosclerosis in apolipoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Using this model, we found that mice with MsrA deficiency were more susceptible to cerebral ischemia/reperfusion injury and were protected by administration of a pharmacological NF-κB inhibitor prior to ischemia (Figure 5 and Figure 6). These findings are concordant with previous studies demonstrating an important role of MsrA in inflammation and NF-κB regulation in atherosclerosis (16) and ischemia/reperfusion injury in myocardium (18). Our observation that NF-κB activation contributes to the increased susceptibility of MsrA −/− mice to cerebral ischemia/reperfusion injury also is consistent with a recent report implicating MsrA in protection from NF-κB activation in rat microglia in a model of neuroinflammation induced by lipopolysaccharide (22).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Using this model, we found that mice with MsrA deficiency were more susceptible to cerebral ischemia/reperfusion injury and were protected by administration of a pharmacological NF-κB inhibitor prior to ischemia (Figure 5 and Figure 6). These findings are concordant with previous studies demonstrating an important role of MsrA in inflammation and NF-κB regulation in atherosclerosis (16) and ischemia/reperfusion injury in myocardium (18). Our observation that NF-κB activation contributes to the increased susceptibility of MsrA −/− mice to cerebral ischemia/reperfusion injury also is consistent with a recent report implicating MsrA in protection from NF-κB activation in rat microglia in a model of neuroinflammation induced by lipopolysaccharide (22).…”
Section: Discussionsupporting
confidence: 93%
“…These findings suggest that protein methionine oxidation is a key pathological mechanism of reperfusion injury during acute ischemic stroke. Potential therapeutic approaches to target this pathway may include MsrA mimetics (16, 22), CaMKII inhibitors (64), and NF-κB pathway modulators.…”
Section: Discussionmentioning
confidence: 99%
“…Although CPPs have been used as vectors for delivery of drugs [48][49][50][51], other peptides of therapeutic potential [52][53][54][55][56][57][58][59][60], proteins [56,[61][62][63][64][65], radioisotopes [66][67][68][69], quantum dots [70,71] and photosensitizers [72,73], this review will focus on use of CPPs as vectors for nucleic acid delivery, be they genes, oligonucleotides, peptide nucleic acid conjugates, small interfering RNA (siRNA) or the newest application with DNA origami. Although there is literature on all of these applications, most interest and work done to date has been with siRNA.…”
Section: Cell Penetrating Peptides As Gene Delivery Vectorsmentioning
confidence: 99%
“…For atherosclerosis analysis, the entirety of the aorta was fixed in 4% paraformaldehyde, opened longitudinally and then analyzed en face. The aortic root slides were determined by Oil Red O (ORO) staining and quantification by Image J software as described preciously [19].…”
Section: Histochemical and Immunohistochemistry Of Atherosclerotic Lementioning
confidence: 99%